Analysis of push and pull factors in food travel motivation. Issue 5 (3rd March 2020) - Su, Diep Ngoc; Johnson, Lester W.; O'Mahony, Barry
ABSTRACT: With a lack of a comprehensive understanding of travel motivation toward a food destination, this study aims to identify internal motives of potential food tourists and their preferred destination attributes by adopting the push–pull framework. A survey was conducted via online networks of 'foodies' yielding 335 valid responses. Results of exploratory factor analyses and measurement model evaluations indicated three push factors: taste of food, socialization and cultural experiences; and three pull factors: core food-tourism appeals, traditional food appeals and local destination appeals. The results contribute to our understanding of food travel motivation from both a tourist and a destination perspective. Practical managerial implications for Destination Management Organizations (DMOs) are also provided.